Participation in innovation platform and asset acquisitions among farmers in Southern Africa - Adeolu B. Ayanwale; Adewale A. Adekunle; Ayodeji D. Kehinde; Oluwole A. Fatunbi (Environmental and Sustainability Indicators, 2023)
Asset development is a crucial tactic for advancing social and economic development in Southern Africa. But until now, there has not been any solid evidence of how asset-building strategies affect Southern African households. This study investigates the relationship between participation in innovation platforms and the acquisition of assets among farmers. Data for the study were collected using a multistage sampling approach. The data were analyzed using the Endogenous Treatment Linear Regression model. According to the findings of the first regression (Probit regression), gender, marital status, years of education, number of male working-class members, number of female working-class members, number of aged dependents in the household, access to extension service and locational effect of farmers in Mozambique have a significant relationship with the participation of farmers in Innovation Platforms. The results of the endogenous treatment linear model for asset acquisition among farmers reveal gender, age, marital status, number of male-working class members, access to extension service, the locational effect of farmers in Mozambique, and participation in the activities of the Innovation Platform are all statistically significant. After controlling for observed and unobserved covariates, the study concluded that participation in the activities of Innovation Platforms has a positive relationship with the acquisition of assets among the farmers than they would have in the absence of participation in Innovation Platforms. Therefore, farmers need to enhance their asset base by participating in Innovation Platforms. This has a significant implication for the attainment of most of the targets of the SDG.